Where will the animals stay? - Calmenson, Stephanie (New York : Parents Magazine Press, 1983)
Zoo animals needing a place to stay temporarily are offered an apartment house.
Keywords: Zoo animals -- Fiction; Apartment houses -- Fiction; Stories in rhyme